Academic Learning Time Investment In Some Organized Games’ Lessons and Its Relation With Direct and Indirect Learning - Daraa, Ahlam (Journal of Physical Education, 2019)
The aim of the research is to specifying the percentage of time investment during the main part of organized games lesson. In addition to that it aims at comparing among them to identify the relation between direct and indirect learning on students. The researcher used the descriptive method on Sophomore College of physical education and sport sciences students / university of Mosel. She used Anderson form to conclude that there are preferences in time distribution of students’ behavior during the main part of team sports lessons (basketball – volleyball – handball). Volleyball got the highest percentage in indirect learning followed by handball then basketball. The researcher recommended the necessity of using teaching methods and styles that achieve response and interaction between the students and the teacher as well as among students themselves so as to develop organized games learning. She also recommended paying attention to time distribution during learning in the main part of the lesson so as to save time and effort.